2019
DOI: 10.7717/peerj.7540
|View full text |Cite
|
Sign up to set email alerts
|

RFRP3 influences basal lamina degradation, cellular death, and progesterone secretion in cultured preantral ovarian follicles from the domestic cat

Abstract: The hypothalamic neuropeptide RFRP3 can suppress hypothalamic GnRH neuron activation and inhibit gonadotropin release from the anterior pituitary. RFRP3 is also produced locally in the ovary and can inhibit steroidogenesis and follicle development in many vertebrates. However, almost nothing is known about the presence and regulatory action of RFRP3 in gonads of any carnivore species. Such knowledge is important for developing captive breeding programs for endangered carnivores and for inhibiting reproduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Non-seasonal breeders include spontaneous ovulating species, such as humans, rats, mice, and naked mole rats, as well as induced ovulating species, such as the domestic cat. Unlike short-day and long-day breeders, the literature on non-seasonal breeders is more consistent, and GnIH and its receptor were shown to be present in all three levels of the HPG axis ( 13 , 15 , 30 , 35 , 105 ). Interestingly, puberty in humans has been hypothesized to be better anticipated by measuring the accumulation of fat rather than using age or environmental stimuli as a predictor ( 106 ).…”
Section: Gnih and Its Receptor In The Brain Involvement In Multiple Neuroendocrine Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-seasonal breeders include spontaneous ovulating species, such as humans, rats, mice, and naked mole rats, as well as induced ovulating species, such as the domestic cat. Unlike short-day and long-day breeders, the literature on non-seasonal breeders is more consistent, and GnIH and its receptor were shown to be present in all three levels of the HPG axis ( 13 , 15 , 30 , 35 , 105 ). Interestingly, puberty in humans has been hypothesized to be better anticipated by measuring the accumulation of fat rather than using age or environmental stimuli as a predictor ( 106 ).…”
Section: Gnih and Its Receptor In The Brain Involvement In Multiple Neuroendocrine Systemsmentioning
confidence: 99%
“…Although it is clear that GnIH and its receptor are key to the hypothalamic control of reproduction, the presence of the GnIH-R at the lower level of the HPG axis (gonads) has also been reported in avian species, including the Japanese quail, the European starling, the white-crowned sparrow ( 10 ), and the domestic chicken ( 7 , 230 ), as well as various fish species including clownfish ( 57 ), Nile tilapia ( 56 ), Indian carp ( 61 ), common carp ( 54 ), zebrafish ( 51 ), and goldfish ( 49 ), and the rat ( 13 , 15 ). Additionally, the GnIH-R has been identified in the ovary of humans ( 30 ), swine ( 33 ), felines ( 35 ), tongue sole ( 60 ), and in the testis of Syrian hamsters ( 26 ) and house sparrows ( 11 ) ( Table 1 ). Furthermore, treatment with GnIH was shown to effectively shut down reproduction in the ovary and testis not only by indirectly reducing gonadotropins release from the pituitary as previously discussed, but also directly by decreasing cell viability in the ovary and reducing the levels of testosterone in the testis ( 5 , 8 , 10 , 11 , 46 , 51 ).…”
Section: Beyond Neuroendocrine Functions Gnih and Its Receptor Participate In The Peripheral Regulation Of Physiological Processesmentioning
confidence: 99%
“…Previous studies confirmed that the GnIH receptor GPR147, also named NPFF receptor 1, is considered a novel member of the G-protein-coupled receptors [ 50 ]. The interaction between GnIH/RFRP-3 and GPR147 is known from studies of their mRNA and protein expression profiles in cat and rat ovarian cells [ 45 , 51 ]. Biochemical examination demonstrated that RFRP-3 has a greater affinity with GPR147, so GPR147 is one of the major receptors for RFRP-3 [ 50 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Kisspeptin at a concentration of 100 nM decreases granulosa cell viability [ 28 ]. In addition, RFRP-3 has been reported to decrease the number of estrous cycles in cold-stressed rats [ 29 ], and to decrease follicular viability in cats [ 30 ]. Follicles’ exposure to 1 μM of RFRP-3 increased the proportion of follicles with cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Follicles’ exposure to 1 μM of RFRP-3 increased the proportion of follicles with cell death. One of the mechanisms proposed by the authors is that RFRP-3 can promote follicular degradation through paracrine signaling [ 30 ]. Additionally, RFRP-3 has been reported to decrease porcine granulosa cell viability at different concentrations [ 31 ].…”
Section: Discussionmentioning
confidence: 99%